Sources of Added Sugars Intake Among the U.S. Population: Analysis by Selected Sociodemographic Factors Using the National Health and Nutrition Examination Survey 2011–18 - Ricciuto, Laurie; Fulgoni, Victor L.; Gaine, P. Courtney; Scott, Maria O.; DiFrancesco, Loretta (Frontiers in Nutrition, 2021)
Recent estimates of added sugars intake among the U.S. population show intakes are above recommended levels. Knowledge about the sources of added sugars contributing to intakes is required to inform dietary guidance, and understanding how those sources vary across sociodemographic subgroups could also help to target guidance. The purpose of this study was to provide a comprehensive update on sources of added sugars among the U.S. population, and to examine variations in sources according to sociodemographic factors. Regression analyses on day 1 intake data from NHANES 2011-18 was used to examine sources of added sugars intake among the full sample (N=30,678) and among subsamples stratified by age, gender, ethnicity, and income. Results showed the majority of added sugars in the diet (61-66%) came from a few sources, and the top two sources were sweetened beverages and sweet bakery products, regardless of age, ethnicity, or income. Sweetened beverages, including soft drinks and fruit drinks, as well as tea, were the largest contributors to added sugars intake. There were some age-, ethnic-, and income-related differences in the relative contributions of added sugars sources, highlighting the need to consider sociodemographic contexts when developing dietary guidance or other supports for healthy eating.